Pengukuran Produktivitas Pada Produk Plastik untuk Meningkatan Daya Saing - Suhartini Suhartini; Mochammad Basjir (Jurnal Serambi Engineering, 2022)
PT. XYZ is a manufacturing company engaged in plastic products. In the production process, problems occur in the cutting machine. Cutting machines often experience acceleration in the setup process. The purpose of the study was to determine the value of the productivity index and evaluate the value to increase the productivity of the company. This study uses the American Productivity Center method and the productivity Evaluation Tree. The results showed that the productivity index value of the American Productivity Center showed an increase and decrease in the value of the productivity index. The increase in the total value of productivity inputs occurred in March 2020 by 190%. Meanwhile, the productivity value decreased in December 2020 by 181%. The Productivity Evaluation Tree method results experienced a change in the total production value in 2019 of 1.75 and the total production value in 2020 of 1.51.